(untitled) (Interdisciplinary Studies Journal, 2024)
Interpreting scientific terms on industrialized product labels is a complex task, requiring the ability to relate scientific concepts to their practical application. However, this challenging exercise plays a crucial role in encouraging a broader reflection on the presence of science in the social context. In this context, this study aims to analyze the coherence of scientific terms on shampoo labels and propose pedagogical strategies that can contribute to the development of science teaching oriented towards a critical perspective. To achieve this, we chose to adopt an exploratory qualitative methodological approach. We analyzed the terms salicylic acid, piroctone olamine, wheat protein, coconut oil and panthenol. To support our analysis, we used information from scientific articles evaluating the effectiveness of these components in solving hair problems such as seborrheic dermatitis and psoriasis. At the end of this study, we present proposals that aim to foster a critical approach to scientific knowledge, enabling students to understand the products in question and the science behind them.